Effect of probiotics on mother-to-neonate vertical transmission of group B streptococci: A prospective open-label randomized study - Yuriha Kasai; Mitsutaka Komatsu; Yudai Toyama; Saki Nakano; Ken Hisata; Mie Yamada; Toshiaki Shimizu (Pediatrics and Neonatology)
Background: Group B Streptococci (GBS) are common vaginal bacteria found in 20–30% of pregnant women and a significant cause of invasive infections in newborns. Recently, attention has been focused on the efficacy of probiotics during the perinatal period. However, the effect of probiotic intake on the mother-to-child transmission (MTCT) of GBS remains unknown. Methods: Pregnant women with positive GBS results from vaginal and rectal swab cultures at 35–37 weeks of gestation were randomly assigned to the probiotic group or the control group in an open-label manner at the Department of Obstetrics and Gynecology, San-ikukai Hospital, Tokyo, Japan. The probiotic group received Lactobacillus reuteri during antenatal checkups from 35 to 37-week gestation to 1 month after delivery. Rectal swabs were obtained from the newborns at 5 days and at 1 month of age. Whole-genome sequencing was performed to test for GBS strains in the mother, whose newborn carried GBS at the 1-month checkup. Multi-locus sequence typing and single nucleotide polymorphism analyses were performed to identify MTCT. Results: Overall, 67 mother-infant pairs were included, with 31 in the probiotic group and 36 in the control group. The positivity rate of GBS in newborns at 1 month of age was 10% (n = 3) in the probiotic group and 28% (n = 10) in the control group. In newborns carrying GBS at 1 month of age, genetic analysis revealed that the MTCT rate was 6% in the probiotic group and 22% in the control group, although the difference was not statistically significant (p = 0.0927). Conclusion: No statistically significant difference was found; however, the consumption of L. reuteri by women with GBS-positive pregnancies may inhibit the MTCT of GBS.